Differences in the association between empirically derived dietary patterns and cancer: a meta-analysis. (19th May 2017) - Bella, Francesca; Godos, Justyna; Ippolito, Antonella; Di Prima, Alessia; Sciacca, Salvatore
Abstract: Plant-based dietary patterns have been associated with decreased cancer risk. The aim of the present study was to perform a meta-analysis of studies comparing empirically derived dietary patterns in relation to cancer risk. A systematic search of PubMed and EMBASE electronic databases was conducted. Eligible studies had an observational design and evaluated the association with cancer risk between a posteriori derived dietary patterns. Random-effects models were applied to calculate relative risks (RRs) of cancer between diets. Statistical heterogeneity and publication bias were explored. An increased risk of cancer for the adoption of high-meat compared to plant-based dietary patterns was found (RR =1.64, 95% CI: 1.02, 2.63). Lower risk of cancer for individuals adopting a plant-based dietary pattern over a mixed one was found (RR =0.88, 95% CI: 0.82, 0.95). In conclusion, plant-based dietary patterns can be considered a healthy choice over meat-based dietary patterns.